Optimization of resources in forage production Irrigation District 028 Tulancingo - Torres Suárez, Sandra Luz; Tijerina Chávez, Leonardo; Ibáñez Castillo, Laura Alicia; Bautista Hernández, Martha (Revista Mexicana de Ciencias Agrícolas, 2020)
The limitation of resources in forage production, necessary for the development of livestock production activity in irrigation district 028 Tulancingo, in the state of Hidalgo, motivated the development of a linear programming model (LPM) that optimizes them in quantity total required. In this model, with the Simplex method, the objective function was to maximize the total net economic benefit (BN) of the district; starting from the sum of the BN of each crop by its surface, thus generating a pattern that complies with the total restrictions to which the function is subject: availability of resources and requirements of each crop. Based on the generated LPM, four scenarios were tested: 1) current situation; 2) with coating of the conduction network; 3) with second cultures; and 4) with coating and second cultures. Each one with four variants of water availability: the one registered in the 2018-2017 agricultural cycle, those calculated for exceedance probability of 50, 75 and 95%. The combination of scenarios and variants resulted in a total of 16 cultivation patterns in which, as the volume offered is reduced, the maximum areas that the LPM suggest for each cultivation are also reduced. The actions proposed in scenarios 2, 3 and 4 in all cases increased the feasible area as well as the BN compared to the current situation, even though this presents a greater availability of water.
Keywords: crop pattern; linear programming; net profit